Neural changes in reward processing following approach-avoidance training for depression. Issue 3 (13th October 2021) - Bomyea, Jessica; Choi, Soo-Hee; Sweet, Alison; Stein, Murray; Paulus, Martin; Taylor, Charles
Abstract: Altered approach motivation is hypothesized to be critical for the maintenance of depression. Computer-administered approach-avoidance training programs to increase approach action tendencies toward positive stimuli produce beneficial outcomes. However, there have been few studies examining neural changes following approach-avoidance training. Participants with major depressive disorder were randomized to an approach-avoidance training (AAT) manipulation intended to increase approach tendencies for positive social cues ( n  = 13) or a control procedure ( n  = 15). We examined changes in neural activation (primary outcome) and connectivity patterns using Group Iterative Multiple Model Estimation during a social reward anticipation task (exploratory). A laboratory-based social affiliation task was also administered following the manipulation to measure affect during anticipation of real-world social activity. Individuals in the AAT group demonstrated increased activation in reward processing regions during social reward anticipation relative to the control group from pre- to post-training. Following training, connectivity patterns across reward regions were observed in the full sample and connectivity between the medial prefrontal cortex and caudate was associated with anticipatory positive affect before the social interaction. Preliminary evidence of differential connectivity patterns between the two groups also emerged. Results support models whereby modifying approach-oriented behavioral tendencies with computerized training lead to alterations in reward circuitry (NCT02330744).